Functional groups of microcrustaceans along a horizontal gradient in a Neotropical lake colonized by macrophytes - Coelho, Paula Nunes [UNESP]; Henry, Raoul [UNESP] (Springer Nature, 2021)
Here we analysed the taxonomic and functional diversity of microcrustaceans along a horizontal gradient from the littoral to pelagic zones of a marginal lake. We hypothesized that in the littoral zone, occupied by high density of macrophytes, the taxonomic and functional diversity would be higher because the macrophytes coverage offers greater availability of niches for microcrustaceans. The individuals were collected in 10 sampling stations in a horizontal transect from littoral to pelagic zones of the lake. The community structure was determined by three classic measures: species richness, diversity and abundance of organisms. For the measurement of functional diversity, we identified the functional groups and calculated the functional group richness, the indexes of functional richness (FRic) and functional evenness (FEve). The abundance of microcrustaceans was higher in littoral zone, while the species richness and diversity did not differ between the zones of the lake. Cyclopoid copepod nauplii predominated in the region with macrophytes, while adult forms increased in pelagic zone. For functional diversity, the community was divided in six functional groups, with bosminids dominating the lake. Values of FRic and FEve did not differ between the regions of the lake, but the functional groups were more diverse in the littoral zone. The habitat complexity offered by macrophytes in the littoral zone provides greater diversification of ecological niches for microcrustaceans, resulting in more diverse functional groups. Finally, functional diversity proved to be a more accurate tool in detecting spatial variations in the microcrustacean community when compared to the taxonomic diversity.
Keywords: Cladocera; Copepoda; Functional diversity; Littoral and pelagic zones; Zooplankton